The XBI BioLab for life science experiments at the European XFEL. Issue 1 (2nd December 2020) - Han, Huijong; Round, Ekaterina; Schubert, Robin; Gül, Yasmin; Makroczyová, Jana; Meza, Domingo; Heuser, Philipp; Aepfelbacher, Martin; Barák, Imrich; Betzel, Christian; Fromme, Petra; Kursula, Inari; et al.
Abstract : An overview of a unique life science facility at the European XFEL is provided, and its importance in sample preparation, characterization and analysis prior to measurements at the different European XFEL instruments is discussed. The capabilities that the facility can provide for the research community are highlighted, alongside examples of recent successful studies. Abstract : The science of X‐ray free‐electron lasers (XFELs) critically depends on the performance of the X‐ray laser and on the quality of the samples placed into the X‐ray beam. The stability of biological samples is limited and key biomolecular transformations occur on short timescales. Experiments in biology require a support laboratory in the immediate vicinity of the beamlines. The XBI BioLab of the European XFEL (XBI denotes XFEL Biology Infrastructure) is an integrated user facility connected to the beamlines for supporting a wide range of biological experiments. The laboratory was financed and built by a collaboration between the European XFEL and the XBI User Consortium, whose members come from Finland, Germany, the Slovak Republic, Sweden and the USA, with observers from Denmark and the Russian Federation. Arranged around a central wet laboratory, the XBI BioLab provides facilities for sample preparation and scoring, laboratories for growing prokaryotic and eukaryotic cells, a Bio Safety Level 2 laboratory, sample purification and characterization facilities, a crystallization laboratory, an anaerobic laboratory, an aerosol laboratory, a vacuum laboratory for injector tests, and laboratories for optical microscopy, atomic force microscopy and electron microscopy. Here, an overview of the XBI facility is given and some of the results of the first user experiments are highlighted.